O efeito da realidade aumentada na experiência do consumidor varejista - Silva Neto, Genésio Renovato da (2023)
Digital transformation has impacted retail in the last decade and augmented reality (AR) has been used in applications as an important means of improving the retail consumer experience. AR is a technology that offers fun and interactivity in the purchase process, which is significant for the consumer experience. AR provides an integration of digital content in coexistence with the consumer's environment in real time, which facilitates the visualization of the product as an overlay on the real world. The present study aimed to examine the effect of augmented reality on the retail consumer experience, and to what extent these factors impact on the perception of value, satisfaction, and purchase intention. This is a quantitative research, descriptive approach, and positivist paradigm, with the strategy of field research, in person in an environment prepared and controlled for the use of the AR application. Based on the collection of primary data through survey research, using questionnaires based on scales to collect information. The target audience of the survey were 368 retail consumers who had already purchased at least once online through (website or application). The results indicate that the consumer experience is more consistent when AR is the main interaction channel and that AR applications promoted a positive effect on purchase intention due to the possibility of having a more complete experience. The positive experience linked to interactivity is an important path for purchase intention and consumers tend to have a higher level of satisfaction when the purchase journey is made up of interactivity and fun. It was observed that the limitation of personalization can have a negative effect on the consumer. In the proposed mediations, AR partially mediated interactivity and consumer experience. However, interactivity had a stronger direct effect on the experience. It was found that the experience mediated the relationship between AR and satisfaction, proving to be a stronger path. Likewise, consumer experience mediated the reaction between augmented reality and purchase intention. It is concluded in this study that AR can influence the consumer experience through immersion, interactivity, and product projection, reducing the perception of space between virtual and real. The experience in the purchase journey is especially important to promote satisfaction and purchase intent.